Blackening of Pompeian cinnabar paintings: X-ray microspectroscopy analysis - Cotte, Marine; Susini, Jean; Metrich, Nicole; Moscato, Alessandra; Gratziu, Corrado; Bertagnini, Antonella; Pagano, Mario (Analytical chemistry (Washington), 2006)
Red Pompeian paintings, very famous for their deep intensity, are currently suffering from darkening. The origins of this darkening degradation are not clearly identified yet and remain a major issue for curators. In the specific case of cinnabar (HgS)-based red pigment, a photoinduced conversion into black metacinnabar is usually suspected. This work is focused on the blackening of red cinnabar paintings coated on a sparry calcite mortar. Different samples exhibiting different levels of degradation were selected upon visual observations and analyzed by synchrotron-based microanalytical techniques. Atomic and molecular compositions of the different debased regions revealed two possible degradation mechanisms. On one hand, micro X-ray fluorescence elemental maps show peculiar distributions of chlorine and sulfur. On the other hand, X-ray absorption spectroscopy performed at both Cl and S K-edges confirms the presence of characteristic degradation products: (i) Hg-Cl compounds (e.g., corderoite, calomel, and terlinguaite), which may result from the reaction with exogenous NaCl, in gray areas; (ii) gypsum, produced by the calcite sulfation, in black coatings. Metacinnabar is never detected. Finally, a cross section was analyzed to map the in-depth alteration gradient. Reduced and oxidized sulfur distributions reveal that the sulfated black coating consists of a approximately 5-mum-thick layer covering intact cinnabar.